Some Physical and Mechanical Properties of Plum Tree (Prunus Domestica L.) - Slavko Govorčin (University of Zagreb, Faculty of Forestry and Wood Technology, 2012)
Plum (Prunus domestica L.) is one of the most widespread species of fruit trees in South-East Europe. Because of its fruits, it has been cultivated for centuries. The emergence of plum pox virus caused the disappearance of a large number of „old“ plum sorts. There is no chemical agent to combat plum pox virus, and the only way to prevent the spread of the virus is to destroy plantations. For this reason there is a large amount of wood mass that can be used for industrial purposes. In Croatia, over the past years we have witnessed this process that slowly spreads along the territory of Bosnia and Herzegovina and other countries in the region. In this research some physical and mechanical properties were studied of plum wood from middle Bosnia and Herzegovina. The results of this research can be used to determine technological properties of plum wood. The physical properties of plum wood that were studied are as follows: density in absolutely dry condition, nominal density, total longitudinal, radial, tangential and volumetric shrinkage. The mechanical property of plum wood that was studied is: ultimate tensile stress parallel to the grain. From macroscopic characteristics, growth ring was measured for the correlation with the studied physical and mechanical properties of plum wood. Mean density in absolutely dry condition is 0.705 g/cm3, and mean value of conventional density is 0.619 g/cm3. Mean value of the total longitudinal shrinkage is 0.3 %, total radial shrinkage is 4.8 %, total tangential shrinkage is 7.5 %, and mean value of the total volumetric shrinkage is 12.1 %. Mean value of the ultimate tensile stress parallel to the grain at 12 % water content is 101.9 MPa.